SYNONYMIC AND ANTONYMIC TRANSLATION (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article explores the concepts of synonymic and antonymic translation, highlighting their significance as strategies for achieving linguistic and cultural equivalence in translation. It defines synonymic translation as the process of replacing a source language word with a synonym in the target language to preserve meaning while adapting the text to the target culture. Antonymic translation, on the other hand, involves substituting a word with its opposite, often requiring adjustments to the surrounding context to maintain the original message. The article emphasizes the importance of these techniques in literary, marketing, and cross-cultural communication, noting their challenges, such as the potential for subtle differences in meaning and cultural misrepresentation. Ultimately, the article illustrates that both techniques offer creative solutions for overcoming the complexities of translation, ensuring that the essence of the original text resonates with diverse audiences.